An optimal iterative learning control approach for linear systems with nonuniform trial lengths under input constraints - Zhuang, Zhihe; Tao, Hongfeng; Chen, Yiyang; Stojanovic, Vladimir; Paszke, Wojciech (1975- )
In practical applications of iterative learning control (ILC), the repetitive process may end up early by accident during the performance improvement along the trial axis, which yields the nonuniform trial length problem. For such practical systems, input signals are usually constrained because of some certain physical limitations.
Keywords: nonuniform trial length; iterative learning control; optimal control